The prolongation of somatic support in a pregnant woman with brain-death: a case report - Amaral Eliana; Cecatti José G; Surita Fernanda; Oliveira-Neto Antonio; Souza João P; Pinto e Silva João L (BMC, 2006)
Abstract Background Medical literature has increasingly reported cases of maternal brain death during pregnancy. This is a rare situation which demands the decision and, depending on the gestational age, the implementation of a set of measures to prolong the homeostasis of the human body after brain death for the purpose of maintaining the foetus alive until its viability. Case presentation A 40 year old woman suffered an intracranial haemorrhage during the 25th week of pregnancy. Despite neurosurgical drainage of a gross intraparenchymatous haematoma, the patient developed brain death. Upon confirmation of this diagnosis, she received full ventilatory and nutritional support, vasoactive drugs, maintenance of normothermia, hormone replacement and other supportive measures required to prolong gestation and improve the survival prognosis of her foetus. All decisions regarding the patient's treatment were taken in consensus with her family. She also received corticosteroids to accelerate foetal lung maturity. During the twenty-five days of somatic support, the woman's condition remained stable; however, during the last seven days the foetus developed oligohydramnios and brain-sparring, which led the medical team to take the decision to perform a Caesarean section at that moment. After delivery, the patient's organs were removed for donation. The male infant was born weighing 815 g, with an Apgar score of 9 and 10 at the first and fifth minutes, respectively. The infant was admitted to the neonatal intensive care unit, but did not require mechanical ventilation and had no major complications. He was discharged at 40 days of life, with no sequelae and weighing 1850 g. Conclusion These results are in accordance with findings from previous studies and case reports suggesting the appropriateness and safety of extended somatic support during pregnancy under certain circumstances. They also suggest the need for prompt diagnosis of brain death before the occurrence of physiological degeneration, rapid evaluation of foetal status and the decision of the family together with the medical team to prolong maternal somatic support. The occurrence of maternal brain death is a tragedy, but it may also represent a challenging opportunity to save the life of the foetus and, in addition, permit donation of the maternal organs.